Deformation mechanism of hard elastic polyethylene film during uniaxial stretching: Effect of stretching speed. (12th September 2019) - Lin, Yuanfei; Li, Xueyu; Chen, Xiaowei; An, Minfang; Zhang, Qianlei; Wang, Daoliang; Chen, Wei; Yin, Panchao; Meng, Lingpu; Li, Liangbin
Abstract: The effects of stretching speed on the structural evolutions and mechanical behaviors of hard-elastic polyethylene films are studied with in-situ and ex-situ small-angle X-ray scattering (SAXS), scanning electronic microscope (SEM) and tensile tests in a wide stretching speed range (0.04–4 mm/s). Based on the evolutions of structural parameters extracted from SAXS results and the surface morphologies from SEM experiments, the stretching speed space can be divided into two regions with the boundary of 0.8 mm/s. Stress induced microphase separation of amorphous phase triggers the yielding behavior, which distributes more homogeneously with the increase of stretching speed. In region I, microphase separation tends to develop into cavities at smaller strain due to the thorough relaxation process of molecular chains in amorphous phases, which results in the inhomogeneous deformation during further stretching. In region II, the relaxation of molecular chains is not enough to response to the variation of external tensile field, thus inducing the uniform distribution of the occurrence of microphase separation. Graphical abstract: Image 1 Highlights: Effect of stretching speed on structures and mechanical property was studied. Stretching speed is of importance in how microphase separation occurs and develops. The deformation is inhomogeneous at low stretching speed region I. Plastic deformation occurs earlier at low stretching speed.